Current studies of immunotherapy in head and neck cancer. (29th May 2017) - Dogan, V.; Rieckmann, T.; Münscher, A.; Busch, C.‐J.
Abstract : Background: Recently, enormous progress in cancer therapy has been achieved by the use of immune checkpoint inhibitors. Activating the body's own immune system has added a novel and powerful therapeutic option for the treatment of melanoma and lung cancer. Furthermore, the potential use of immunotherapy is being extensively explored also in other malignancies. Objective of review: This review summarises current clinical studies using immune checkpoint modulators for the treatment of head and neck cancer (HNSCC). Type of review: Systematic review. Search strategy: A PubMed search from 2010 onwards was performed for the use of immune checkpoint inhibitors in clinical trials of HNSCC. An equivalent search was performed at clinicaltrials.gov. Additionally, the abstracts from the annual meetings of the ASCO, ESMO and AACR were screened. Results: A total of 45 relevant studies using immune checkpoint inhibitors in HNSCC were identified. In the majority of these studies, antagonistic antibodies targeting the immune checkpoint receptors PD‐1 are used either solely or combined, mostly with other immunomodulatory antibodies, such as inhibitors of CTLA‐4. Most studies are still recruiting patients (26/45). In the primary setting, we identified 16 studies using checkpoint inhibition as neoadjuvant/adjuvant modality for treatment with curative intent. The response rate upon treatment with PD‐1 antagonists in relation to the PD‐L1 status is being investigated in 12 trials. Novel immune checkpoint modulators combined with the inhibition of the PD‐1/PD‐L1 axis or CTLA‐4 have been set up in six trials. So far, only four studies that use immune checkpoint inhibition in HNSCC have presented results and all of these explored the inhibition of the PD‐1/PD‐L1 axis. The studies demonstrated overall response rates (ORR) in the range of 20%. These preliminary data suggest that a PD‐L1 expression ≥1% is associated with a higher response rate compared to a PD‐L1 expression ≤1%. The anti‐PD‐1‐antibody pembrolizumab extended the duration of response in recurrent and/or metastatic (R/M) HNSCC (by approximately 53 weeks) in a phase Ib study. Therefore, pembrolizumab was granted accelerated approval for the treatment of platinum refractory R/M HNSCC by the FDA. Conclusion: Numerous clinical trials are addressing the suitability and efficacy of immune checkpoint modulators in HNSCC with the predominant targets being the established immune checkpoint receptors PD‐1/PD‐L1 and CTLA‐4. Recently, presented results have shown a survival benefit, a favourable safety profile and an extended duration of response in favour of using immune checkpoint modulation in R/M HNSCC.